Project-Based Approach in Botany Education: Identifying Local Flora Using DNA Barcoding and Bioinformatics - Amonovich, Shamsiyev Naim; Qodirov, Azizjon (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2025)
Traditional botany education is often limited to plant identification based on morphological characteristics and classical herbarium collection. In this research, we propose an innovative, project-based learning (PBL) model aimed at developing students' scientific research competencies in teaching botany. The model integrates classical field botany, modern DNA barcoding technology, and bioinformatics analysis. Throughout the project, students collected samples from local flora, described them morphologically, and then generated DNA barcodes using standard loci such as rbcL and matK. The obtained sequences were analyzed using online databases such as BLAST and BOLD. The research showed that this approach not only deepens students' theoretical knowledge in species concepts, phylogenetics, and bioinformatics, but also develops practical skills essential for 21st-century specialists, such as critical thinking, problem-solving, and teamwork. This model significantly increases educational effectiveness by connecting the learning process with scientific discovery.